(3OjhGf GdCYTis - (3CHhHUjQ ejehf Hf bjS Hf LfOd GdhGFdi CYTi bjSs ((3GHhGdYHGS CMeO Hf jMji KYdH s)
(3ChdgG (B:s
((3bGd GdCYTi(B: (3ejehf Hf bjS(B) (3GHf LfOd Hf TQGMjd jeOM GdCShO Hf GdefPQ eG HcGA GdcHjQ HGdCWdGd hSDGdj agd JQO SDGdj s
(3BNQgG (B:s
(3UMG GdbdH Yf PcQ bJjdI HYOeG jchf dgG eKd GdCSQ GdecHd aOYgG hSqd Gdge YfgG HLSQI JRHO aj aVd GdReGe hJbJd s
(3fSNI KGfjIs
(3HgG BKGQ MQjbs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B30 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B776s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd , eHJhQI GdBNQ s
Keywords: (3GdCOHs